India's Social Structure, Arranged Marriage, and the Power of Love - Dr. Giri Gupta Raj Pal, (Al-Qanṭara, 2023)
Using testimonies posted on Shaadi.com, this essay examines how women from the Indian diaspora express their views on love and marriage. Arranged marriage and love marriage are frequently seen as being incompatible in the literature on Indian marital customs. Nonetheless, this essay makes the case that women in the Indian diaspora are beginning to conceptualise marriage differently. Data from Shaadi.com specifically indicate that portrayals of marriage on the website are dominated by the merged practise known as "planned love marriages." The results of the theme analysis of 208 testimonies show that Uberoi's (1998, 2006) theory of an arranged love marriage is pervasive in the narratives looked at. The way families behave has changed significantly in recent decades. One example of this is the drop in planned marriages and parallel rise in "love marriages"—more precisely, self-chosen marriages—across Asia. In the past, arranged marriages—where parents select their children's spouses—were common in many Asian nations. However, in recent years, young people in Nepal (Fricke et al. 1998, Ghimire et al. 2006, Niraula 1994), Indonesia (Malhotra 1991), China (Pimentel 2000), Taiwan (Thornton and Lin 1994), Japan (Applbaum 1995), Korea, and Malaysia have been more active in selecting their own marriages (Rindfuss and Morgan 1983). The study of such changes—their causes, how they occur, and the effects they have—represents a significant area of sociological inquiry. recent studies on family transitions.